Understanding individuals' subjective experiences of negative symptoms of schizophrenia: A qualitative study. (3rd April 2020) - Butcher, Isabelle; Berry, Katherine; Haddock, Gillian
Abstract : Objectives: Individuals with a diagnosis of schizophrenia often experience both positive and negative symptoms. Negative symptoms can be disabling and have a serious impact on everyday functioning. Despite the range of clinician‐rated measurement tools used to assess negative symptoms, very little is known about how individuals subjectively experience these symptoms. This study sought to examine, using qualitative methods, how people living with a diagnosis of schizophrenia subjectively experience negative symptoms. Design: Qualitative study. Method: Semi‐structured interviews were carried out with individuals with a diagnosis of schizophrenia who were experiencing negative symptoms. The sample was recruited from community and inpatient National Health Service mental health settings in the United Kingdom. Interviews were analysed using thematic analysis. Results: Twenty individuals took part. Individuals highlighted the persistent and enduring nature of their negative symptoms. Two central themes were identified: What it is like to experience negative symptoms and where have my negative symptoms come from? Within the first theme, four sub‐themes emerged: loss of concentration, loss of motivation, withdrawal, and 'feeling but not feeling'. Within the second theme, four sub‐themes emerged related to the causes of negative symptoms: impact of traumatic life events, positive psychotic symptoms, impact of social network, and recreational and prescribed drug use. Conclusion: Individuals, who experience negative symptoms, were able to articulate the persistent and disabling nature of negative symptoms and clearly described factors which they believed contributed to the onset, exacerbation, and amelioration of the experiences. Practitioner points: Negative symptoms for people diagnosed with schizophrenia are persistent and enduring and impact an individual's life. There has been little research conducted qualitatively on individuals' subjective experiences of negative symptoms. Individuals who experience negative symptoms attribute these to a number of factors, including adverse life events, recreational and prescribed drug use, an absence of social support, and positive psychotic symptoms. Understanding negative symptoms is important for services, clinicians, and family members, where misattributions made about negative symptoms can lead to such experiences being dismissed.